Protein O-Fucosyltransferase 2 Is Not Essential for Plasmodium berghei Development - Sanz, Silvia; Aquilini, Eleonora; Tweedell, Rebecca E.; Verma, Garima; Hamerly, Timothy; Hritzo, Bernadette; Tripathi, Abhai; Machado, Marta; Churcher, Thomas S.; Rodrigues, João A.; Izquierdo, Luis; Dinglasan, Rhoel R. (Frontiers in Cellular and Infection Microbiology, 2019)
Thrombospondin type I repeat (TSR) domains are commonly O-fucosylated by protein O-fucosyltransferase 2 (PoFUT2), and this modification is required for optimal folding and secretion of TSR-containing proteins. The human malaria parasite Plasmodium falciparum expresses proteins containing TSR domains, such as the thrombospondin-related anonymous protein (TRAP) and circumsporozoite surface protein (CSP), which are O-fucosylated. TRAP and CSP are present on the surface of sporozoites and play essential roles in mosquito and human host invasion processes during the transmission stages. Here, we have generated PoFUT2 null-mutant P. falciparum and Plasmodium berghei (rodent) malaria parasites and, by phenotyping them throughout their complete life cycle, we show that PoFUT2 disruption does not affect the growth through the mosquito stages for both species. However, contrary to what has been described previously by others, P. berghei PoFUT2 null mutant sporozoites showed no deleterious motility phenotypes and successfully established blood stage infection in mice. This unexpected result indicates that the importance of O-fucosylation of TSR domains may differ between human and RODENT malaria parasites; complicating our understanding of glycosylation modifications in malaria biology.